TEACHERS' QUESTIONS IN ENGLISH LANGUAGE TEACHING (ELT) CLASSES - Kshetree, Arun Kumar; Jyoti, Rameshwar (Universitas Negeri Gorontalo, 2024)
In discussions about how students are questioned in English Language Teaching (ELT) classrooms, there is an emphasis on different questioning types and purposes that are still relatively new in many Nepali classroom settings. In this context, this study was conducted to explore secondary level English teachers' practices of questioning the students in the classrooms. The study adopted a qualitative research design. For this, eight secondary level English teachers from four community schools of Arghakhanchi, Dang, Palpa and Rupandehi districts in Lumbini Province were selected as informants. The data were elicited through classroom observation and semi-structured interviews. First, classroom observation of eight teachers was carried out. Then, they were interviewed. Analysis of qualitative data uncovered that the majority of the teachers adopted higher-order, lower-order, and follow-up types of questions to create interactive environments in the classrooms and develop their communicative skills. In addition, the data also revealed that the teachers asked the students some brainstorming and critical thinking questions to enhance their critical thinking ability. Moreover, the data demonstrated that most of the students preferred to be asked questions while a few of them were afraid of making mistakes while answering verbally. Furthermore, it was also explored that sometimes with a shout and angry mood, the students were asked unsuitable and irrelevant questions about the topics. Additionally, the data mirrored that when the students were asked questions engaging them in interactions, they got motivated and ready to respond without any hesitation. This study contributes to the understanding of English teachers about the ways and purposes of questioning to enhance students' performance in the English language